Location, migration and age: Literary clusters in Germany from mid-18th to early-20th Century - Lukas Kuld; John O'Hagan (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2019)
We study the formation of creative clusters in the light of the changes in theGerman economic and political structures during the 19th century. We show how themigration and geographic location of writers mirrors the evolution of the literary market froma patronage system in a pre-industrial, politically fractured area to a market system in amodern nation state. For this, we have collected yearly data on the 149 German writers listedin the Encyclopedia Britannica and born in the 18th and 19th centuries. We find that, first,large cities, especially Berlin, become the dominant location though only at the end of thisprocess. Second, migration and publication output are both strongly linked to age. These age-migration and age-productivity patterns remain for subsequent cohorts. However, while later-born writers spend their formative and most productive years close to other writers, there isno clear cluster pattern for earlier writers
Keywords: 330; geographic clusters; migration; creative output; age